Sustainability and Human Resources Management: Evaluating Challenges and Impacts for the Employee-Organization Relation - Daniel Roque Gomes; ?Neuza Ribeiro; Maria Jo\~ao Santos (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Although sustainability is hardly a new subject for research, recent years have moved the theme toward the perspective of human resource management (HRM). In effect, it has become a recent target of attention for HRM researchers in the search for valid ways to stimulate the area and be committed and resourceful regarding structural paths leading to overall sustainable development. Consequently, identifying the way in which sustainable human resource management (SHRM) practices that support organizational strategy, performance, or internal development can and should be devised has become a challenge of investigation. HRM has always been a management area permeable to new challenges aimed at enhancing organizational productivity, internal efficiency, or organizational strategic development. Sharing this alignment with the new millennium development agenda, the area has recently been influenced by research dedicated to understanding in what ways sustainability can work alongside HRM to achieve structural progress for organizations.
Keywords: 650; green human resource management; bibliometric analysis; sustainability; green practices; corporate social responsibility; CSR perceptions; environment-related CSR; employee-related CSR; customer-related CSR; organizational identification; organizational citizenship behavior; hotels; ESG management; ESG activity recognition; innovative organization culture; job crafting; job performance; knowledge management; employee retention; telecom; flexible working arrangements; supervisor support; coworker support; online teaching; faculty; well-being; sustainable HRM; work engagement; turnover intention; Nigeria; green transformational leadership; green human resource management practices; employees' green behavior; small and medium enterprises; corporate sustainability; triple bottom line; natural resource-based view; sustainable human resources management; internal communication; attractiveness; performance; hospitality; hotel employee; human resource management; job satisfaction; organizational communication; perceived organizational support; travel and tourism; voluntary employee turnover; empowerment; motivation; meaning; self determination